2018
DOI: 10.37358/rc.18.9.6577
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Eugenol Effects on the Bioenergetic Profile of SCC-4 Human Squamous Cell Carcinoma Cell Line

Abstract: Eugenol (EU), the active ingredient in clove oil, is commonly used as successful therapeutic compound in dentistry due to its antiseptic and anti-inflammatory effects. Recent research studies suggest that eugenol has also a potential anti-cancer effect. This study was thereby purported to assess the effects of EU on the bioenergetic profile of the SCC-4 human squamous cell carcinoma cell line. To this aim, SCC-4 cells were treated for 24 hours with free EU and EU incorporated in polyurethane structures (50 �M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In line with these observations, we aimed to investigate the effect of eugenol, free, or encapsulated in polyurethane nanoformulations [ 25 ], on both mitochondrial bioenergetics and glycolysis in SCC-4 human squamous cell carcinoma cells by means of the extracellular flux analyzer Seahorse XF24e (Agilent Technologies Inc.). This automatic platform provides a simultaneous measurement of oxygen consumption rate (OCR) as an indicator of mitochondrial respiration, and the extracellular acidification rate (ECAR) as an indirect measurement of anaerobic glycolysis, according to a previously described method [ 116 ]. In brief, cellular metabolic activity was challenged with the classic modulators of the mitochondrial electron transport chain: the first automatic injection was performed using oligomycin (1 μ g/ml), the inhibitor of the mitochondrial ATP synthase; FCCP (3 μ M), a classic uncoupler, was further injected, followed by antimycin A (5 μ M), the inhibitor of mitochondrial complex III.…”
Section: Protective Cellular Effects Of Eugenol: a Bird's Eye Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these observations, we aimed to investigate the effect of eugenol, free, or encapsulated in polyurethane nanoformulations [ 25 ], on both mitochondrial bioenergetics and glycolysis in SCC-4 human squamous cell carcinoma cells by means of the extracellular flux analyzer Seahorse XF24e (Agilent Technologies Inc.). This automatic platform provides a simultaneous measurement of oxygen consumption rate (OCR) as an indicator of mitochondrial respiration, and the extracellular acidification rate (ECAR) as an indirect measurement of anaerobic glycolysis, according to a previously described method [ 116 ]. In brief, cellular metabolic activity was challenged with the classic modulators of the mitochondrial electron transport chain: the first automatic injection was performed using oligomycin (1 μ g/ml), the inhibitor of the mitochondrial ATP synthase; FCCP (3 μ M), a classic uncoupler, was further injected, followed by antimycin A (5 μ M), the inhibitor of mitochondrial complex III.…”
Section: Protective Cellular Effects Of Eugenol: a Bird's Eye Viewmentioning
confidence: 99%
“…OCR was reported in units of pmoles/min and ECAR in mpH/min. SCC-4 human squamous carcinoma cells were incubated for 24 h with eugenol (free or incorporated in polyurethane structures), and we found that free eugenol (50 μ M) induced a decrease of OCR parameters (i.e., inhibition of mitochondrial respiration) coupled with an increase of ECAR (i.e., stimulation of glycolysis); surprisingly, opposite effects were recorded for eugenol nanoformulations, i.e., an increase in basal and maximal respiration (OCR) plus a decrease in glycolysis (ECAR) [ 116 ]. The effects of free eugenol are in line with the abovepresented literature data, yet the paradoxical effect of nanostructures requires further investigations.…”
Section: Protective Cellular Effects Of Eugenol: a Bird's Eye Viewmentioning
confidence: 99%